Ozone and nitrogen dioxide regulate similar gene expression responses in Arabidopsis but natural variation in the extent of cell death is likely controlled by different genetic loci - Leppälä, Johanna; Gaupels, Frank; Xu, Enjun; Morales, Luis O.; Durner, Jörg; Brosché, Mikael (Frontiers in Plant Science, 2022)
High doses of ozone (O3) and nitrogen dioxide (NO2) cause damage and cell death in plants. These two gases are among the most harmful air pollutants for ecosystems and therefore it is important to understand how plant resistance or sensitivity to these gases work at the molecular level and its genetic control. We compared transcriptome data from O3 and NO2 fumigations to other cell death related treatments, as well as individual marker gene transcript level in different Arabidopsis thaliana accessions. Our analysis revealed that O3 and NO2 trigger very similar gene expression responses that include genes involved in pathogen resistance, cell death and ethylene signaling. However, we also identified exceptions, for example RBOHF encoding a reactive oxygen species producing RESPIRATORY BURST OXIDASE PROTEIN F. This gene had increased transcript levels by O3 but decreased transcript levels by NO2, showing that plants can identify each of the gases separately and activate distinct signaling pathways. To understand the genetics, we conducted a genome wide association study (GWAS) on O3 and NO2 tolerance of natural Arabidopsis accessions. Sensitivity to both gases seem to be controlled by several independent small effect loci and we did not find an overlap in the significantly associated regions. Further characterization of the GWAS candidate loci identified new regulators of O3 and NO2 induced cell death including ABH1, a protein that functions in abscisic acid signaling, mRNA splicing and miRNA processing. The GWAS results will facilitate further characterization of the control of programmed cell death and differences between oxidative and nitrosative stress in plants.